Implementasi Mata Kuliah Microteaching Dalam Pembentukan Keterampilan Mengajar Mahasiswa Prodi Pendidikan Agama Islam Jurusan Tarbiyah Dan Keguruan Angkatan 2021 Sekolah Tinggi Agama Islam Negeri (STAIN) Majene - Jelita; Usri; Nihla Afdaliah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Microteaching has an important role in shaping prospective educators, so its implementation is recommended to take place thoroughly. The purpose of this study was to describe the implementation of microteaching courses in the formation of teaching skills of 2021 batch students of Tarbiyah and Keguruan PAI Study Program at STAIN Majene. This type of research uses qualitative research with a phenomenological approach method, researchers obtain data from observation, interviews and documentation. The results showed that, there are six steps in the implementation of microteaching courses consisting of: (1) introduction to the concept of microteaching which is carried out at the beginning of the lecture by providing structured material, so that students can form teaching skills ranging from opening to closing skills. (2) presentation of models and discussions, where the supervisor uses various methods such as lectures, discussions, questions and answers, hands-on practice, and preparation of papers Through this process, students can form skills ranging from choosing a model or learning method, explaining material, asking questions to managing the class. (3) planning or preparation for teaching by preparing lesson plans or modules in this case, students can form skills ranging from opening to closing lessons, 4) the implementation of teaching practice which has four groups with observers and five groups without observers, this aims to shape students' skills from opening to closing lessons, (5) feedback discussions are carried out through oral and written observations by students as well as supervisors' assessments of lesson plans and teaching practices through this process, students can form motivational skills. However, there are important steps that cannot be implemented due to time constraints, namely the practice of relearning. In addition, some shortcomings were also found in certain classes such as the feedback given was less specific, the absence of an assessment sheet and the unavailability of a semester implementation plan (RPS).